2015
DOI: 10.1007/s40292-015-0106-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Hypertension and Body Mass Index and Waist Circumference in U.S. Adults: A Comparative Analysis by Gender

Abstract: BMI and WC may influence hypertension differently among males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 37 publications
2
16
0
Order By: Relevance
“…However, whether exercise alone could affect abdominal obesity or blood pressure was not validated because lifestyle factors were not adjusted in the program. Similarly, in the previous studies that analyzed the association between baseline waist circumference and hypertension risk, adjustment for physical activity did not affect the association between abdominal obesity and hypertension . In our study, we observed that, even though this was not an intervention study, baseline physical activity did not affect the deleterious effects of abdominal obesity on incident hypertension.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, whether exercise alone could affect abdominal obesity or blood pressure was not validated because lifestyle factors were not adjusted in the program. Similarly, in the previous studies that analyzed the association between baseline waist circumference and hypertension risk, adjustment for physical activity did not affect the association between abdominal obesity and hypertension . In our study, we observed that, even though this was not an intervention study, baseline physical activity did not affect the deleterious effects of abdominal obesity on incident hypertension.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, in the previous studies that analyzed the association between baseline waist circumference and hypertension risk, adjustment for physical activity did not affect the association between abdominal obesity and hypertension. 8,25,26 In our study, we observed that, even though this was not an intervention study, baseline physical activity did not affect the deleterious effects of abdominal obesity on incident hypertension. Thus, in preventing hypertension, prompt treatment of abdominal obesity is more important than solely being physically active.…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, to the best of our knowledge, there is still no evidence of a significant association between hypertension and LSG histopathology. As for a potential confounder's association to the exposure under examination, BMI was significantly associated with HTN [29], DM2 [30], H. pylori [31], gender [32] and age [32]. The current study used multivariable regression analysis to control for such identified confounders during data analysis, as recommended by others [33].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of hypertension adjusted for age, sex and country of origin was similar in PLHIV and in the general population. However, after further adjustment for BMI, a strong predictor of hypertension [42], it becomes evident that in fact, PLHIV have higher prevalence of hypertension, compared to the general population.…”
Section: Hiv-infected Predicted % (95% Ci)mentioning
confidence: 99%